Organic Electroactive Molecule-Based Electrolytes for Redox Flow Batteries: Status and Challenges of Molecular Design - Zhong, Fangfang; Yang, Minghui; Ding, Mei; Jia, Chuankun (Frontiers in Chemistry, 2020)
This is a critical review of the advances in molecular design of organic electroactive molecules which are the key components for redox flow batteries (RFBs). As a most potential large-scale energy storage system, redox flow battery is attracting increasing attention in last decades. The redox molecules, which bridge the interconversion between chemical energy and electric energy for RFBs generate wide interests in many fields such as energy storage, function materials and synthetic chemistry. The widely used electroactive molecules are inorganic metal ions, most of which are scarce and high cost hindering the broad deployment of RFBs. Thus, to exploit novel cost-effective electroactive molecules are urgently motivated by the commercialization of RFBs. RFBs based on organic electroactive molecules, such as quinones and nitroxide radical derivatives have been studied and been as one of hot topics due to inherent merits in the last decade. However, comprehensive summaries in view of molecular design of organic electroactive molecules are not frequently reported. Herein, the latest progress and challenges of organic electroactive molecules in both non-aqueous and aqueous RFBs are reviewed, and future perspectives have been put forward for further developments of RFBs as well as other electrochemical energy storage systems.